Mapping the Digital Transformation of Microfinance: A Systematic Literature Review - Chaity, Naznin Sultana; Rahaman, Mahabubur (European Scientific Journal, ESJ, 2026)
Digital transformation is reshaping microfinance institutions worldwide. This article presents a systematic literature review examining the multidimensional impact of digital transformation on microfinance. The LENS.org scholarly database was selected as the primary data source, and Journal articles published between 2018 and 2024 were collected for this study. A total of 1,000 documents were collected, and after application of the exclusion and inclusion criteria, 562 articles were included in this study. Prisma flowchart, Keyword co-occurrence analysis, citation analysis, and descriptive statistics were used for this study. Findings confirm 7 clusters identified that Institutional capacity, regulatory quality, digital infrastructure, and sociocultural contexts are identified as critical moderating conditions that determine whether digital transformation generates inclusive or exclusionary outcomes. The COVID-19 pandemic was found to be a powerful accelerant of digital adoption among the microfinance institutions. The research community was mainly urged to pursue longitudinal, comparative, and interdisciplinary methodologies to strengthen the evidence base. Evidence-based collaboration among policymakers, institutions, technologists, civil society, and researchers may be needed to support more digitized microfinance institutions.